CRISPR-Cas-Based Antimicrobials: Design, Challenges, and Bacterial Mechanisms of Resistance - Mayorga-Ramos, Arianna; Zúñiga-Miranda, Johana; Carrera-Pacheco, Saskya E.; Barba-Ostria, Carlos; Guamán, Linda P. (ACS infectious diseases, 2023)
The emergence of antibiotic-resistant bacterial strains is a source of public health concern across the globe. As the discovery of new conventional antibiotics has stalled significantly over the past decade, there is an urgency to develop novel approaches to address drug resistance in infectious diseases. The use of a CRISPR-Cas-based system for the precise elimination of targeted bacterial populations holds promise as an innovative approach for new antimicrobial agent design. The CRISPR-Cas targeting system is celebrated for its high versatility and specificity, offering an excellent opportunity to fight antibiotic resistance in pathogens by selectively inactivating genes involved in antibiotic resistance, biofilm formation, pathogenicity, virulence, or bacterial viability. The CRISPR-Cas strategy can enact antimicrobial effects by two approaches: inactivation of chromosomal genes or curing of plasmids encoding antibiotic resistance. In this Review, we provide an overview of the main CRISPR-Cas systems utilized for the creation of these antimicrobials, as well as highlighting promising studies in the field. We also offer a detailed discussion about the most commonly used mechanisms for CRISPR-Cas delivery: bacteriophages, nanoparticles, and conjugative plasmids. Lastly, we address possible mechanisms of interference that should be considered during the intelligent design of these novel approaches.